A Quantitative Structure-Activity Relationship and Molecular Modeling Study on a Series of Biaryl Imidazole Derivatives Acting as H+/K+-ATPase Inhibitors. (14th February 2013) - Agarwal, Neeraj; Bajpai, Anubha; Srivastava, Vivek; Gupta, Satya P.
Abstract : The H + /K + -ATPase or proton pump is a magnesium-dependant enzyme which causes the exchange of a proton against a potassium ion through a membrane. Over activity of this enzyme causes hyperacidity by producing more of hydrochloric acid inside the stomach. This enzyme, therefore, has been found to be a good target for designing compounds to treat hyperacidity. A quantitative structure-activity relationship (QSAR) study has been made on a novel series of biaryl imidazole derivatives acting as H + /K + -ATPase inhibitors. The H + /K + -ATPase inhibition activity of these compounds is found to be significantly correlated with global topological charge indices (GTCIs) and the total polar surface area (TPSA) of the molecules, indicating the involvement of strong electronic interaction between the molecule and the receptor. Based on the correlations obtained, some new H + /K + -ATPase inhibitors are predicted. The docking studies of these predicted compounds exhibit that these compounds will have even better interaction with the receptor than those already marketed. Thus, they can prove more potent drugs for the treatment of hyperacidity.